2001
DOI: 10.1126/science.1059707
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Aerobic Photoheterotrophic Bacteria to the Carbon Cycle in the Ocean

Abstract: The vertical distribution of bacteriochlorophyll a, the numbers of infrared fluorescent cells, and the variable fluorescence signal at 880 nanometers wavelength, all indicate that photosynthetically competent anoxygenic phototrophic bacteria are abundant in the upper open ocean and comprise at least 11% of the total microbial community. These organisms are facultative photoheterotrophs, metabolizing organic carbon when available, but are capable of photosynthetic light utilization when organic carbon is scarce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

26
415
9
3

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 399 publications
(453 citation statements)
references
References 24 publications
26
415
9
3
Order By: Relevance
“…The values (up to 3.1 ng l −1 ) are consistent with other studies of oligotrophic environments (Cottrell et al, 2006;Kolber et al, 2001;Schwalbach and Fuhrman, 2005;Sieracki et al, 2006). Both AAP bacterial abundance and BChl-a concentrations significantly decreased with increasing longitude and oligotrophy from west to east, though both varied less with location than with depth.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…The values (up to 3.1 ng l −1 ) are consistent with other studies of oligotrophic environments (Cottrell et al, 2006;Kolber et al, 2001;Schwalbach and Fuhrman, 2005;Sieracki et al, 2006). Both AAP bacterial abundance and BChl-a concentrations significantly decreased with increasing longitude and oligotrophy from west to east, though both varied less with location than with depth.…”
Section: Discussionsupporting
confidence: 80%
“…AAP bacteria were found to be more abundant in the upper layers of the photic zone than below the sunlit layers of the water column of the Mediterranean Sea. Other studies also reported that AAP bacteria are major bacterial components in the photic zone, in agreement with their phototrophic abilities (Cottrell et al, 2006;Kolber et al, 2001).…”
Section: Bacterial Productionsupporting
confidence: 58%
See 2 more Smart Citations
“…This organism is a close phylogenetical relative of aerobic anoxygentic phototrophs. Aerobic anoxygenic phototrophs are estimated to comprise 11% of the microbial community in the ocean and have been implicated in as much as 5-10% of the photosynthetic potential in the oceans (Kolber et al 2001;Goericke 2002). Because of their important role in the oceans, understanding how this group of organisms may oxidize Mn(II) is especially intriguing and relevant.…”
Section: Introductionmentioning
confidence: 99%